Efektivitas Terapi Spiritual Emotional Freedom Technique Pada Konsentrasi Belajar Anak Usia Dini di Pendidikan Anak Usia Dini Diniyah Putri Lampung - Mu’asyara, Nesia; Padilla, Rahmi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Spiritual Emotional Freedom Technique (SEFT) therapy is a combination of spiritual power and energy psychology. The working principle of this therapy is almost similar to acupuncture therapy, as it utilizes meridian points. The difference is that SEFT therapy harnesses spiritual power in the form of prayer, sincerity, and surrender to God. There are two most important aspects of SEFT therapy: positive affirmations and tapping. Positive affirmations help achieve good emotional health in early childhood. These affirmations can strengthen and influence positive behavior. Tapping involves light taps on acupoints on the body. When the body is stimulated with light taps, the response is an increase in the mobility of signals, which leads to a decrease in hypothalamic regulation and a reduction in the production of the stress hormone cortisol. The research approach chosen is a quantitative approach with an experimental research design. This study was conducted at PAUD Diniyyah Putri Lampung. The research sample consisted of 60 individuals, using the pretest-posttest control group design method. The aim of this research is to determine the effectiveness of SEFT therapy on the learning concentration of early childhood in PAUD Diniyyah Putri Lampung. The analysis technique used is the independent sample t-test with a significance level of 0.05. Based on the independent sample t-test conducted, the results showed a significance value of p = 0.00 < 0.05. Thus, it can be concluded that SEFT therapy is effective in improving the learning concentration of early childhood in PAUD Diniyyah Putri Lampung.